DIVERSITY OF INTERNAL TRANSCRIBED SPACER (ITS) REGION OF FUSARIUM ISOLATES IN PAKISTAN - R. Ghaffar; W. Anwar; K. Imtiaz; M. Shafiq; M. N. Subhani; M. S. Haider (Journal of Animal and Plant Sciences, 2016)
The present study evaluate the genetic diversity analysis of the ITS regions of rRNA gene complex of local isolates of Fusarium in Pakistan. The genomic DNA of these isolates was amplified using primers ITS1 and ITS4 designed at the end, and start of conserved 18S and 28S region and between ITS1 and ITS4 respectively. By the comparison of RG2, RG3, RG4, RG5, RG6, and RG9 all species have higher genetic diversity while RG2 and RG6 have highest homology with each other that showed that both may be originated from same ancestor. Morphological and molecular data obtained might be useful in determining the taxonomy and diversity of Fusarium species. Results obtained reveals inter specific variation among the isolated organisms with limited intra specific variability. It can therefore be inferred based on findings that ITS analysis could provide taxonomic evidence for the isolated organisms but may not be informative enough to score diversity.
Keywords: ITS region; Genetic diversity; Fusarium; BLAST; CLC BIO; CTAB